Even employees are undertakings in the labour market, but granting social rights is not antitrust's job. (7th January 2022) - Maggiolino, Mariateresa
Abstract: The lively debate about the right of gig workers to bargain collectively stems from the idea that European Union (EU) competition law treats this group of workers worse than it treats employees. Namely, it is common to argue that employees, unlike gig workers, are permitted to conclude collective agreements because they are not undertakings and, therefore, not subject to EU competition law. In sharp contrast, by analysing the EU notion of undertaking, this article demonstrates—and this is the first of its theses—that in the labour market, which is the market that should matter in relation to the effects of collective agreements, employees are as much undertakings as any other worker, such as gig workers or other self-employed workers. The article further maintains that the reason employees are currently allowed to bargain collectively, while other workers are not, is to be found not within competition law, but outside it. At present, employees' collective agreements are exempt from the application of EU competition law because employees enjoy the right to bargain collectively, among other social rights, and because the Court of Justice of the European Union has (rightly) recognized that the protection of these rights must trump the protection of competition. Consequently, this article argues, as its second thesis, that if Articles 151–161 TFEU were interpreted so as to grant social rights to workers other than employees, the collective agreements of gig workers and other under-protected self-employed workers would be exempt from EU competition law, as are those of employees. At the same time, however, this paper recognizes that, in the absence of such an interpretative turn, antitrust legislators and policy makers could aid gig workers and other under-protected self-employed workers by excluding them and their collective agreements from the scope of application of competition law. This—and here is the third thesis of the article—would not force the interpretation of antitrust notions and rules and would thus not require antitrust authorities and courts to use competition law to pursue goals different from the protection of efficiency and innovation.